FAKTOR YANG MEMPENGARUHI KEPATUHAN PENGOBATAN PENDERITA HIPERTENSI USIA PRODUKTIF DI DESA KARANGSONO KECAMATAN BARAT KABUPATEN MAGETAN - Dara Aprilia Aurilita Mawanti; Avicena Sakufa Marsanti; Hanifah Ardiani (J-KESMAS: Jurnal Kesehatan Masyarakat, 2020)
In 2018, Karangsono Village is village with the highest number of medication incompliance by hypertension patients at productive age reaching 70,7% compared to other 8 villages in Tebon Health Center working area. This research for to analyze factors affecting the medication compliance of hypertension patients at productive age and factor which affects the medication compliance the most. This research was done through case control design with the research samples included 58 chosen using simple random sampling. The data was then analyzed using chi-square statistical test and logistic regression statistic.Results : Through the analysis using logistic regression test, it shows that the factors affecting the medication compliance by the hypertension patients at productive age in Karangsono Village, Barat Sub-District were working status (p=0.000), family support (p=0.001), and the length of time of the hypertension suffering (p=0.016).Conclusion : Among those factors, working status is the factor which affects the medication compliance the most (p=0.000; Exp(B)=9.9; 95%CI=2.379-36.505). The hypertension medication compliance therapy needs to be improved by providing drug hypertension card independently, while for the patients who can visit the public health center, they were suggested to join the posbindu.